Postexercise Arterial Compliance and Hemodynamic Responses to Various Durations and Intensities of Aerobic Exercise - Karabulut, Murat; Bitting, Margarita; Bejar, Jorge (Journal of strength and conditioning research, 2023)
Karabulut, M, Bitting, M, and Bejar, J. Postexercise arterial compliance and hemodynamic responses to various durations and intensities of aerobic exercise. J Strength Cond Res 37(3): 589-596, 2023-The purpose of this study was to determine the effects of various aerobic training protocols using different intensities and durations on arterial compliance and hemodynamic responses. Seventeen male subjects (age = 23.1 ± 2.8 years) performed a maximal oxygen consumption (V̇ o2 max) test, followed by 3 randomly assigned exercise test sessions, each on a separate day. At the beginning of each test session, pre-exercise baseline assessments of arterial elasticity, hemodynamic variables, and pulse wave velocity (PWV) were performed after a 10-minute rest. After baseline measurements, participants performed either a bout of aerobic exercise on a treadmill for 60 minutes at 65% of V̇ o2 max (60min); 20 minutes at 40% of V̇ o2 max (20min); or for 20 minutes at 40% of V̇ o2 max with blood flow restriction (BFR; 20min-BFR). All baseline measurements were repeated at the completion of each testing session. Significance for this study was set at p ≤ 0.05. The 60min session resulted in significant increases in small artery elasticity (SAE) compared with the 20min-BFR session ( p < 0.03) and decreases in both systemic vascular resistance (SVR) and total vascular impedance (TVI) compared with both 20min sessions ( p < 0.01). The carotid to radial PWV was significantly lower after both the 60min and the 20min-BFR sessions compared with the 20min session ( p < 0.02). The findings indicate that the duration and the intensity of exercise are important factors for improving SAE, SVR, and TVI. In addition, 20min-BFR at 40% V̇ o2 max may result in site-specific modifications in PWV that is comparable with those seen after 60 minutes of exercise at 65% V̇ o2 max.